Engineering bacterial theranostics: from logic gates to in vivo applications - Armstrong, Angus; Isalan, Mark (Frontiers in Bioengineering and Biotechnology, 2024)
Over the past two decades, rapid advances in synthetic biology have enabled the design of increasingly intricate and biologically relevant systems with broad applications in healthcare. A growing area of interest is in designing bacteria that sense and respond to endogenous diseaseassociated signals, creating engineered theranostics that function as disease surveyors for human health. In particular, engineered cells hold potential in facilitating greatly enhanced temporal and spatial control over the release of a range of therapeutics. Such systems are particularly useful for targeting challenging, under-drugged disease targets in a more nuanced manner than is currently possible. This review provides an overview of the recent advances in the design, delivery, and dynamics of bacterial theranostics to enable safe, robust, and genetically tractable therapies to treat disease. It outlines the primary challenges in theranostic clinical translation, proposes strategies to overcome these issues, and explores promising future avenues for the field.